PENGARUH PRODUCT KNOWLEDGE, PROMOTION STRATEGY, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN LAPTOP ASUS UNTUK MENDUKUNG PERKULIAHAN PADA MAHASISWA (STUDI KASUS UNIVERSITAS DI DHARMASRAYA) - Fahruri, Rikza Ajib; Wiska, Mayroza; Qurnia Ra’afi H, Anggy (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
Purpose: This research aims to determine The need that must be met to own a laptop means that students can have problems choosing the right laptop for their needs because of the many laptop brands that exist.  (information why this research need to be done), Methods This research method is a quantitative method with primary data collected using a questionnaire and the scale used is a Likert scale, Analysis data: The analysis used in this research is descriptive analysis, validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, t test, f test and determinant coefficient test r., Result and discussions: As this study's findings demonstrate, product knowledge, promotion technique, and price all play a role in influencing consumers' final purchase decisions. The process involves comparing the computed t-value with the t-table and the computed f-value with the f-table. In this case, the calculated t-value is 6.684, which is greater than the t-table value of 1.967. This indicates that product knowledge, the independent variable, has a positive and significant effect on purchasing decisions, the dependent variable. In the case of f-table, the calculated t-value is 2.336, which is greater than 1.967. The results demonstrate that the promotion approach independent variable influences purchasing decisions dependent variable in a positive and statistically significant way, with a calculated t-value of 5.418 and a t-table value of 1.967, respectively. it is evident that the dependent variable of purchase decisions is positively and significantly impacted by the independent variable of pric., Conclusion: The f-value that was computed (197.195 2.63) exceeds both the f-table value (197.195 2.63) and the significance level (0.000 0.05). This suggests that the process is carried out simultaneously, as the result is the rejection of Ho and the acceptance of H4. There is a strong correlation between product knowledge, promotion strategy, and price in influencing university students' purchasing decisions. This research aims to provide valuable input and consideration for Asus laptops.